MENINGKATKAN PENALARAN MATEMATIKA MELALUI PEMBINAAN OLIMPIADE SAINS KOTA/KABUPATEN MATEMATIKA UNTUK SISWA SEKOLAH MENENGAH PERTAMA - Zulkarnain, Ihwan; Masruroh, Aulia (Jurnal Terapan Abdimas, 2020)
Abstract. The main purpose of community service activities is 1) To familiarize students to work on Olympic questions that have a relatively higher level of difficulty, 2) To foster the intention to learn in science lessons and cause the intention to compete in the next year's Olympics, 3) To improve reasoning students in math subjects. To achieve the above objectives, community service activities have been carried out in the form of the City / District Mathematics Science Olympiad (OSK) which was held in the odd semester of the 2018/2019 academic year at the State Junior High School 1 Tamansari Bogor. This activity was attended by 30 students from class VII and VIII who were selected based on mathematical values when UTS and UAS had high scores. The process of achieving the expected guidance can be indicated in three circumstances. The initial situation, the participants are expected to be familiar with the development of OSK Mathematics, but not yet accustomed to practicing questions that have high reasoning, so that their knowledge needs to be motivated and refreshed about Mathematics questions. In the midst of the situation, the participants already had insight into OSK subject matter which had high reasoning, had begun working on the Olympic questions themselves without a coach and had learned the techniques of doing Olympic questions easily. The final situation, participants are expected to be able to confidently work on the questions easily, quickly and thoroughly. Data that has been collected by interview techniques, observations, and tests, then analyzed descriptively. The results of data analysis can be concluded that 1) students become more accustomed to working on Olympic questions that have a relatively higher level of difficulty with questions, 2) The intention of learning students in the field of mathematics becomes higher, 3) There is an increase in students' reasoning seen from the post results test that continues to rise (after being given material).Abstrak. Tujuan utama kegiatan pengabdian mayarakat adalah 1) Untuk membiasakan siswa-siswa mengerjakan soal-soal Olimpiade yang memiliki tingkat kesukaran soal yang relatif lebih tinggi, 2) Untuk menumbuhkan niat belajar pada pelajaran sains dan menimbulkan niat berkompetisi olimpiade tahun selanjutnya, 3) Untuk meningkatkan penalaran peserta didik dalam mata pelajaran matematika. Untuk mencapai tujuan di atas, telah dilakukan kegiatan pengabdian kepada masyarakat dalam bentuk pembinaan Olimpiade Sains Kota/Kabupaten (OSK) Matematika yang diselenggarakan pada semester ganjil tahun pelajaran 2018/2019 bertempat di SMP Negeri 1 Tamansari Bogor. Kegiatan ini diikuti oleh 30 siswa dari kelas VII dan VIII yang terpilih berdasarkan nilai matematika ketika UTS dan UAS memiliki nilai yang tinggi. Proses tercapainya pembinaan yang diharapkan dapat diindikasikan dalam tiga keadaan. Keadaan awal, para peserta diharapkan sudah mengenal tentang pembinaan OSK Matematika, namun belum terbiasa berlatih pada soal yang memiliki penalaran tinggi, sehingga perlu dimotivasi dan disegarkan kembali pengetahuannya tentang soal-soal Matematika. Keadaan pertengahan, peserta sudah punya wawasan materi soal OSK yang memiliki penalaran tinggi, sudah mulai mengerjakan soal-soal Olimpiade sendiri tanpa Pembina serta telah mengetahui teknik-teknik dalam mengerjakan soal Olimpiade dengan mudah. Keadaan akhir, peserta diharapkan dapat dengan percaya diri mengerjakan soal dengan mudah, cepat dan teliti. Data yang telah dikumpulkan dengan teknik wawancara, observasi, dan tes, kemudian dianalisis dengan secara deskriptif. Hasil analisis data dapat disimpulkan bahwa 1) siswa menjadi lebih terbiasa mengerjakan soal-soal olimpiade yang memiliki tingkat kesukaran soal yang relatif lebih tinggi, 2) Niat belajar siswa dalam bidang matematika menjadi lebih tinggi, 3) Adanya peningkatan penalaran peserta didik dilihat dari hasil post test yang terus naik (setelah diberikan materi).